CLOSTRIDIUM BUTYRICUM CAN BE USED AS A POTENTIAL ALTERNATIVE FOR THE ANTIBIOTIC IN CHERRY VALLEY DUCKS - S. Zhuang; F.B. Jiang; Z.X. Jia; R. Yan (Journal of Animal and Plant Sciences, 2015)
The present study was conducted to investigate the effects of Clostridium butyricum inclusion, as an alternative for antibiotic, on growth performance, immunity and oxidative status of Cherry Valley ducks. 240 1-day-old Cherry Valley ducks were randomly allocated to 2 groups with 6 replicates of 20ducks, receiving a basal diet supplemented with zinc bacitracin (40 mg/kg diet, Control group) or Clostridium butyricum (1.0×109cfu/kg diet), for 42 days, respectively. The results indicated that ducks fed diet supplemented with Clostridium butyricum achieved similar growth performance to those given zinc bacitracin inclusion diet (P>0.05). Likewise, the relative weight of immune organs (thymus, spleen and bursa of Fabricius) in two groupsalso showed a high similarity (P>0.05). As expected, Clostridium butyricum inclusion significantly increased serumimmune globulin M (IgM) content when compared with the control at 21 d (P<0.05). However, this beneficial effect was not observed in the concentrations of serum immune globulin G (IgG), immune globulin A (IgA) and complements (P>0.05). The antioxidant capacity in the serum was similar between the two groups. It was suggested that Clostridium butyricum can be used as an alternative for the antibiotic, zinc bacitracin, in Cherry Valley ducks, which was well demonstrated by various parameters measured above.
Keywords: Clostridium butyricum; Zinc bacitracin; Growth; Immunity; Oxidative status; Cherry Valley ducks